Representation : Elections and Beyond - Smith, Rogers M., 1953-; Nagel, Jack H. (Book collections on Project MUSE., 2013)
Featuring twelve essays that engage with national, provincial, and municipal governments across three continents, Representation examines the core elements and challenges of fair, effective political institutions, providing an invaluable roadmap to better democratic representation in the twenty-first century.